Cerebellar Cortical Degeneration in Cattle Poisoned with Solanum spp. in South America: An Epidemiological, Clinicopathological, Pathological, and Toxicological Review - Verdes, Jose M. (2013)
Cattle that consume Solanum bonariense L (= Solanum fastigiatum Willd.) or Solanum paniculatum L. develop a typical cerebellar cortical degeneration characterized by periodic episodes of ataxia, hypermetria, hyperesthesia, head and thoracic limb extension, opisthotonus, nystagmus, and falling to the side or backward. Histological lesions include vacuolation, degeneration, and loss of Purkinje cells. Axonal spheroids, microcavitations, and other changes of Wallerian degeneration in cerebellar granular layer and white matter are also observed. Neurotoxic compounds in Solanum spp. causing neurologic dysfunction in ruminants were not definitively elucidated. The same Solanaceae species are extensively used with culinary purposes or for the treatment of liver and gastrointestinal disorders as hangovers in humans. In the present paper, we review the epidemiology, clinical signs, and pathological hallmarks of poisoning by Solanum —S. bonariense L. (=S. fastigiatum Willd.) and S. paniculatum—with emphasis in histopathology, ultrastructural, and lectin- and immuno-histochemical changes in spontaneous and experimentally poisoned cattle in South America. The current knowledge of the pathogenesis of these bovine cerebellar cortical degenerations is discussed, and some advances in botanical and toxicological aspects of these Solanaceae species are presented, taking into account the potential risk of human poisoning.